SOSIALISASI PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL PADA PELAJAR - Puspasari, Syifaa; Muis, Abdul; Rofieq, Ainur (Universitas Islam 45 Bekasi, 2024)
Sexual violence among students is becoming a major problem, especially in the school environment. Data from the Ministry of Women's Empowerment and Child Protection (KPPA) shows that cases of sexual violence against children are increasing. In 2022 there will be 18 cases of sexual violence in schools. The method used is the Community Service Program related to outreach to MTs students located in Nagasari Village, Serang Baru District, Bekasi Regency. This service aims to socialize the prevention and preventive treatment of sexual violence. The results obtained from community service are that students gain improvement and new understanding regarding the forms, prevention and handling of cases of sexual violence so that students are enthusiastic about protecting themselves from promiscuity.